Evaluasi Komposisi Elemen Lanskap Kandang Peragaan Taman Margasatwa Ragunan Berbasis Preferensi Pengunjung - Sholihin Nafar; Andi Gunawan; Nurhayati (http://arl-faperta.ipb.ac.id/, 2023)
The shifting of the zoo perspective, from entertainment to being more conservation-oriented has brought positive impacts to environmental conservation. However, it also brought conflict where the need in improving animal welfare contradicted the efforts in increasing visitor satisfaction. This research aimed to evaluate the landscape element of zoo exhibits based on visitor preference as an alternative way to pursue a balance between this conflict. This research was conducted in Ragunan Zoo, Indonesia from 2019 to 2022. Two phases of the questionnaire were conducted during the research. The first questionnaire with a total of 99 respondents resulted that tiger, giraffe, and elephant became the most favorite animals. In opposite, snake, crocodile, and long-tailed macaque became the least favorite animals. In addition, the favorite landscape elements of the zoo’s exhibits were trees, water features, and woods/ log piles; while the least favorite landscape elements were stones, toys (environmental enrichment), and shrubs/climber plants. An in-depth questionnaire was conducted with a total of 37 respondents to understand the preference of landscape elements for visitor satisfaction and animal welfare through exhibit design model simulation. The study found that most respondents showed a positive value on high naturalistic exhibit design for animal welfare. However, the value of high naturalistic exhibits was lower when it comes to visitor satisfaction. It indicated that the presence of trees might reduce visitor’s visibility and overall satisfaction. The result of favorite and least favorite landscape elements slightly varies compared to the first questionnaire. Trees and water features became a consistent favorite landscape element, while toys became the least favorite one. However, the result was the opposite in the shrubs/climber plants element, as in this questionnaire, this element had a positive result in the most of evidence. In the case of stone and wood, the result might vary on animal species and the total area of the zoo’s exhibit.